The Legal Reasoning of Judges Behind Determination of Marriage Itsbat Proposal for Siri Marriage Cases (A Study at the Shariyya Court of Banda Aceh) - Fadhlia Fadhlia (Sharia and Law Faculty, 2021)
This study aims to find out what are the judges of the Shariyya (Religious) Court of Banda Aceh rationale when deciding the itsbat (confirmation) of marriage for siri (undocumented) marriage and its legal consequences on this decision. This juridical-empirical research employs two types of data sources: primary and secondary. The information was gathered through the direct interview with the respondent and informants who were selected from purposive sampling. Using qualitative descriptive analysis, it was concluded the judge's determination when dealing with marriage confirmation request were granting, refusing, canceling, revoking or rejecting the proposal. The decision made by the judge has been carefully considered for the sake of common good and also after examined the formal and material requirements. Therefore, a judge has right to grant a proposal of marriages confirmation for an undocumented marriage thus it becomes legal before the law. The applicants can also file a cassation if their proposal were rejected and for the proposal that were declared void/cancelled can make an attempt to reapply. There are some hopes to the government in regard to this matter: first, the government should make strong and firm laws to oblige the citizen to legalize their marriages based on the state law, second, the government needs to take action against illegal practice of Qadhi (Judge) and lastly, it is also urged to disseminate the information about the risk and negative effects of undocumented marriage through a massive campaign to the community.